Kinesthetic Architecture Exploration through Form (KAtF): An AI enhanced kinesthetic learning module / Mohammad Nazrin Zainal Abidin ... [et al.] - Zainal Abidin, Mohammad Nazrin; Arman, Muhammad Faris; Sayed Abul Khair, Sayed Muhammad Aiman; Yuhaniz, Mayamin; Shahbudin, Mohammad Syathir Amini (2024)
Learning Kinesthetic Architecture through Kinesthetic Learning. Architectural education will undergo progressive transformation with the introduction of Kinesthetic Architecture Exploration through Form (KAtF), an innovative module that combines hands-on, physical learning activities with advanced artificial intelligence tools to generate creative ideas and solutions. This paper presents KAtF as an approach to learning kinesthetic architecture, emphasizing creativity, exploration, and technological fluency. At the heart of KAtF is the innovative integration of form-centric hands-on activities with AI-driven design exploration. Students engage in crafting paper sculptures that serve as physical embodiments of architectural forms, allowing for a profound exploration of spatial composition, proportions, and design principles. This form-centric approach fosters creativity and spatial intelligence while providing a tangible platform for architectural expression. This qualitative study investigates the efficacy of integrating kinesthetic learning principles with AI technology in architectural education, utilizing a paper sculpting module and AI prompting tools to facilitate form-centric hands-on learning. This study assesses the impact of this approach on rapid visualization and heuristic ideation among 24 and 81 architectural students in their third and fourth semesters, respectively at Universiti Teknologi MARA (UiTM), Perak Branch, Seri Iskandar Campus. Findings reveal significant improvements in students' visualization capabilities over time, alongside a proliferation of diverse ideas while maintaining originality and direction. The study underscores the importance of preserving the origin of ideas while leveraging technology, advocating for the incorporation of psychomotor skills development alongside AI integration to foster creativity and innovation in architectural design, thereby advancing architectural education holistically.